Research on Pure Mechanical Lifting Pedal Applied to Rail Transit Vehicles. (August 2020) - Zhang, Yingyong; Hou, Zhaozhan; Lin, Xiangli; Xia, Changkai; Yang, Dongjun; Song, Jianwei
Abstract: With the continuous development of rail transit industry, the comfort level of drivers and the flexibility requirements of customers for the different vehicle of console are continuously improved. At present, the lifting pedal has been widely used in the industry, which are hydraulic and electric type. Pure mechanical lifting pedal has not been applied in the rail transit vehicles. Considering the service life and reliability of the products, many customers, especially foreign customers, require the pure mechanical structure to meet the requirements of different vehicle models and meet the requirements of different drivers for the console. This paper proposes a kind of pure mechanical lifting pedal applied to rail transit vehicles, which can meet the adaptability of the console to different vehicle bodies and drivers, and greatly improve the universality and reliability of the application.